Hepatoprotective effect of antidysbiotic drugs in experimental metabolic syndrome - Vasiuk, V. L.; Levitsky, A. P.; Levchenko, E. M. (Journal of Education, Health and Sport, 2017)
Modeling of experimental metabolic syndrome in Wistar male rats was accompanied by a sharp increase in neutrophils/lymphocytes ratio and decrease in the numbers of monocytes in the blood, as well as almost 5-fold increase in the urease activity, a 3-fold decrease in the activity of lysozyme, and significant increase in the levels of inflammatory markers (MDA and elastase) in the liver. A 13-fold increase was observed in the level of dysbiosis in the liver and a significant increase in the alkaline phosphatase activity. Using antidysbiotic drugs (Quertulin, Quertgial and lysozyme) normalized the state of liver.